FACTORS AFFECTING CORPORATE SOCIAL RESPONSIBILITY IMPLEMENTATION OF VIETNAMESE SMALL-MEDIUM ENTERPRISES - Nguyễn Thị Lành; Phạm Thị Ngọc Trâm (Tạp chí Khoa học Đại học Đà Lạt)
Corporate social responsibility is a new concept which has not been widely dicussed and studied in Vietnam. There are some studies which indicate the important roles and the benefits of CSR implementation and the positive relationship between CSR implementation and financial performance. However, these studies only give solutions for improving CSR implementation based on observation and professionals’ opinions. This study explores potential factors which affect CSR implementation in small-medium enterprises (SMEs) in Vietnam. This study tests four factors of human resources, capital, domestic regulation and knowledge of CSR by Binary Logistic. Human resources and capital are noted as main factors that affect the CSR implementation. Human resources have stronger affect than capital on CSR implementation. This results are also consistent with the result of Yeh, Chen and Wu (2014) [10], which indicates that human resources is the main factor affecting the CSR implementation of companies in the Taiwanese stock market.